Pengaruh Gaya Kepemimpinan dan Kompetensi Terhadap Kinerja Karyawan Bagian Keuangan Rumah Sakit Umum Daerah Cibinong - Iriani Lussa; Adriza; Nurmansyah (MES Bogor, 2025)
This study aims to determine the effect of leadership style and competence on the performance of finance department employees at RSUD Cibinong. The research employed a quantitative method with a population and sample of 40 employees. Data collection techniques included observation and questionnaires. Data were analyzed using descriptive statistics, multiple regression, multiple correlation, and the coefficient of determination. The results showed that leadership style had a very strong relationship with performance, with a correlation coefficient of 0.883 and a determination coefficient of 78%. The resulting regression equation was Y = 7.865 + 0.871X1, indicating a positive and significant influence of leadership style on performance. The t-test showed that the t-value was 3.340 > t-table 2.024, confirming the significance of this effect. Competence also had a strong relationship with performance, with a correlation coefficient of 0.767 and a determination coefficient of 58.8%. The regression equation obtained was Y = 12.930 + 0.560X2. The t-test result showed a t-value of 11.386 > t-table 2.024, indicating that competence had a significant influence on performance. Simultaneously, leadership style and competence had a very strong relationship with performance, with a correlation coefficient of 0.825 and a determination coefficient of 68%. The multiple regression equation was Y = 13.276 + 0.319X1 + 0.564X2. The F-test result showed that the F-value was 63.782 > F-table 3.25, indicating that both independent variables together had a significant influence on employee performance.